CHRISTIANIZATION IN NEW ORDER INDONESIA (1965-1998): DISCOURSES, DEBATES AND NEGOTIATIONS - Narciso, Jerson Benia (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2008)
The author offers a discourse analysis of inter-religious relationsduring the New Order (1965-1998) in Indonesia. The relationsbetween the Muslim majority and Christian minority were tense inthis period. Muslims and Christian disagreed on how to interpretthe law concerning freedom of religion and tolerance. Muslimsclaimed that Christians used foreign aid for 'Christianization' and'Westernization. Christians, on the other hand, claimed thatMuslims curtailed the freedom of religion of Christians by acts ofintolerance and violence. Meanwhile, then president Suharto triedto be seen as impartial, for he considered economic prosperitymore important than religion.